Song Processing in the Zebra Finch Auditory Forebrain Reflects Asymmetric Sensitivity to Temporal and Spectral Structure - Van Ruijssevelt, Lisbeth; Washington, Stuart D.; Hamaide, Julie; Verhoye, Marleen; Keliris, Georgios A.; Van der Linden, Annemie (Frontiers in Neuroscience, 2017)
Despite being commonly referenced throughout neuroscientific research on songbirds, reports of hemispheric specialization in the processing of song remain controversial. The notion of such asymmetries in songbirds is further complicated by evidence that both cerebral hemispheres in humans may be specialized for different aspects of speech perception. Some studies suggest that the auditory neural substrates in the left and right hemispheres of humans process temporal and spectral elements within speech sounds, respectively. To determine whether songbirds process their conspecific songs in such a complementary, bilateral manner, we performed functional magnetic resonance imaging (fMRI) on 15 isoflurane anesthetized adult male zebra finches (Taeniopygia guttata) while presenting them with (1) non-manipulated, (2) spectrally-filtered (reduced spectral structure), and (3) temporally-filtered (reduced temporal structure) conspecific song. Our results revealed sensitivity of both primary (Field L) and secondary (caudomedial nidopallium, NCM) auditory regions to changes in spectral and temporal structure of song. On the one hand, temporally-filtered song elicited a bilateral decrease in neural responses compared to the other stimulus types. On the other hand, spectrally filtered song elicited significantly greater responses in left Field L and NCM than temporally filtered or non-manipulated song while concurrently reducing the response relative to non-manipulated song in the right auditory forebrain. The latter hemispheric difference in sensitivity to manipulations of spectral structure in song, suggests that there is an asymmetry in spectral and temporal domain processing in the zebra finch auditory forebrain bearing some resemblance to what has been observed in human auditory cortex.